Análisis de la comercialización de plantas ornamentales de los viveros de Machala en El Oro Ecuador - Armijos Rodriguez, Milton Ramiro (2015)
No information is available on the commercial activity of ornamental plants in the city of Machala, emerging the need for an analysis of this marketing chain, in order to generate and contribute with specific data for society in general, for what was raised the following objectives: (a) analyze the trade in ornamental plants that are sold the nurseries of the city of Machala. (b) to obtain measurable information in the supply of ornamental species marketed in the city of Machala. (c) Identify the market segment that demands more ornamental plants. Using a theoretical methodology descriptive and exploratory, through survey applied to the nurseries of the city to collect the primary information used in the statistical analysis with the graphics that were made for a better comparative interpretation of the results, getting that six of the seven nurseries sell plants from other provinces being the cities of miracle and Santo Domingo where it comes from more than 90% of the ornamental plants, being a marketing chain with few actors but that increases the final price of the product by its high cost in transport. In our study we can say that there are marketing a range of up to 175 plant species, has also been identified that the most frequent visitors to the nurseries are women over 40 years and the preferences is determined by perennial plants with showy flowers such as roses, geraniums, extravagant and bougainvilles laying.